2009
DOI: 10.1590/s0034-70942009000400007
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between The Inspired Fraction Of Oxygen, Maternal Partial Oxygen Pressure, And Fetal Partial Oxygen Pressure During Cesarean Section Of Normal Pregnancies

Abstract: Induction of maternal hyperoxia by the administration of supplementary oxygen did not increase fetal partial oxygen pressure. Fetal gasometric parameters did not change even when maternal parameters changed, induced by hyperoxia, during cesarean section under spinal block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Ten trials were performed in patients undergoing scheduled CD with regional anesthesia and 4 trials were performed in women in labor . One trial included both scheduled CD and emergent CD during labor, and another trial only included patients undergoing emergency CD during labor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten trials were performed in patients undergoing scheduled CD with regional anesthesia and 4 trials were performed in women in labor . One trial included both scheduled CD and emergent CD during labor, and another trial only included patients undergoing emergency CD during labor.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen trials reported results for UA pH—the primary outcome of this review . One of these trials had a cohort of patients randomized at the time of the scheduled CD and another cohort randomized at the time of an emergent CD during labor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study demonstrates that the routine administration of supplemental, low-dose oxygen via a nasal cannula during elective cesarean section under spinal anesthesia has potential benefit in terms of a decreased incidence of maternal desaturation. Maternal desaturation definitions have varied from <95% to <90% [1113], and it has also been defined as a decrease of oxygen saturation of more than 4 percentage points from baseline [14]. We defined maternal desaturation according to the recommendation of O'Driscoll et al [7] and Van de Louw et al, [9] which was an oxygen saturation of <94% and the event occurring more than 30 seconds after probe checking.…”
Section: Discussionmentioning
confidence: 99%